Job strain and symptoms of angina pectoris among British and Finnish middle-aged employees. Issue 12 (26th May 2009) - Lallukka, T; Chandola, T; Hemingway, H; Marmot, M; Lahelma, E; Rahkonen, O
Abstract : Background: High job strain has been linked with cardiovascular outcomes. This study aimed to examine whether job strain is associated with angina pectoris symptoms among British and Finnish non-manual employees. Methods: Postal questionnaire survey data among 40–60-year-old employees of the British Whitehall II Study (n = 4551, 27% women) and the Finnish Helsinki Health Study (n = 7605, 83% women) cohort were analysed. Angina pectoris symptoms were the outcome in logistic regression analysis. Karasek's job strain was examined. Models were adjusted first for age, second for occupational class and finally for smoking, heavy drinking, physical inactivity, unhealthy food habits and obesity. Results: Angina pectoris symptoms were reported by 5% of women and 3% of men in Britain, and by 6% of women and 4% of men in Finland. High job strain was associated with angina pectoris symptoms among men in Britain (OR 2.08; CI 95% 1.07 to 4.02) and women in Finland (OR 1.90; CI 95% 1.36 to 2.63) independent of age, occupational class, and behavioural risk factors. However, similar associations between job strain and angina pectoris symptoms were not observed among men in Finland or women in Britain. Conclusion: The results yielded partial support for the association between job strain and angina pectoris symptoms across national contexts.